Cannabis, an emerging agricultural crop, leads to deforestation and fragmentation. Issue 9 (12th October 2017) - Wang, Ian J; Brenner, Jacob C; Butsic, Van
Abstract : Early assessment of environmental impacts from emerging agriculture is a scientific challenge that – if poorly executed – limits sound policy making. Here, we present an approach for evaluating and forecasting the effects of emerging and expanding land uses on natural habitats. By analyzing landscape change per unit area, the effects of emerging land uses can be compared with established benchmarks. We apply this approach to study forest fragmentation in northern California, comparing the effects of cannabis agriculture – a booming commodity worldwide that affects diverse ecosystems – to those of timber harvest from 2000 to 2013. We found that although timber has greater impacts on the landscape overall, cannabis leads to far greater changes in key metrics on a per‐unit‐area basis. Thus, despite its small current land‐use footprint, if changes are not made in the spatial pattern of its expansion, the boom in cannabis agriculture will likely create substantial threats to the surrounding environment. Future research, land management, and agricultural policy must account for these threats.